A comprehensive review on thermal conductivity and viscosity of nanofluids and their application in heat exchangers - Porgar, Sajjad; Öztop, Hakan Fehmi; Salehfekr, Somayeh (Elsevier, 2023)
Due to their superior thermal and thermophysical properties compared to traditional fluids, as well as their consideration in terms of mass and heat transport, nanofluids today have a variety of uses in numerous in-dustries. The use of nanofluids reduces energy consumption and improves fluid heat efficiency and ultimately makes the size and volume of equipment, which is very important in new technologies. It is important to study the behavior of nanoparticles in basic fluids so. In this paper, a review of the addition of nanoparticles on the thermophysical properties of fluids has been performed, as well as the models that have been proposed so far to measure the thermal conductivity of nanofluids. The results show that increasing the concentration of nano -particles and temperature increases the thermal conductivity. Also, the effect of nanoparticle shape on the thermal conductivity has been investigated and it has been found that non-spherical nanoparticles cause more thermal conductivity in ionic fluid than spherical particles. The temperature ranges between 10 and 250 degrees C and the concentration of 0.01 to 50% were investigated.
Keywords: Nanofluid; Thermophysical properties; Heat exchanger; Correlations